The Idea of the Withering Away of Law in the Early Soviet Legal Philosophy (1917–1930) - G. T. Bogatyrev (Теоретическая и прикладная юриспруденция)
In the legal literature, the traditional idea is that Soviet legal scholars until the early 1930s rationally expected the withering away of law as socialism was being built. In this regard, this article aims to critically review the views on this problem that existed in the USSR and to check if such a theory (group of theories) really existed. To do this, the author checked the internal logic and detailing of the views of some leading Soviet legal philosophers (P. I. Stuchka, E. B. Pashukanis, M. A. Reisner, and I. P. Razumovsky). Their views on the problem of the withering away of the law were also compared with other elements of their scientiﬁc theories and with the provisions of classical Marxism.It has been established that none of the considered works contains a full-ﬂedged scientiﬁc theory of the withering away of law. P. I. Stuchka never supported this idea, and in his works, he wrote about the “withering away” of only certain liberal legal doctrines (freedom of contract, the autonomy of will, etc.). E. B. Pashukanis, known as the most inﬂuential Soviet legal nihilist, argued that the law would be completely replaced by technical norms, but did not provide any explanation for this statement. In many contemporary phenomena of politics and economics, he saw signs of the degradation of law but did not explain in any way how this would lead to the withering away of law itself. The replacement of law by technical norms was also predicted by M. A. Reisner, but his view was even more general — the law should have disappeared by itself when universal equality and justice would have been established in society. The philosopher I. P. Razumovsky also described the withering away of law only in general and, apparently, saw it as nothing more than an ideological stamp.The inability to formulate a detailed theory of the withering away of law, we believe, demonstrates the stability of the Western tradition in the face of many years of determined attempts to deconstruct it.